Early sensing of Yersinia pestis airway infection by bone marrow cells - Vagima, Yaron; Levy, Yinon; Gur, David; Tidhar, Avital; Aftalion, Moshe; Abramovich, Hagar; Zahavy, Eran; Zauberman, Ayelet; Flashner, Yehuda; Shafferman, Avigdor; Mamroud, Emanuelle (Frontiers in Cellular and Infection Microbiology, 2012)
Bacterial infection of the lungs triggers a swift innate immune response that involves the production of cytokines and chemokines that promote recruitment of immune cells from the bone marrow (BM) into the infected tissue and limit the ability of the pathogen to replicate. Recent in vivo studies of pneumonic plague in animal models indicate that the pulmonary pro-inflammatory response to airway infection with Yersinia pestis is substantially delayed in comparison to other pathogens. Consequently, uncontrolled proliferation of the pathogen in the lungs is observed, followed by dissemination to internal organs and death. While the lack of an adequate early immune response in the lung is well described, the response of BM-derived cells is poorly understood. In this study, we show that intranasal (i.n.) infection of mice with a fully virulent Y. pestis strain is sensed early by the BM compartment, resulting in a reduction in CXCR4 levels on BM neutrophils and their subsequent release into the blood 12 hours (h) post infection. In addition, increased levels of BM-derived hematopoietic stem and progenitor cells (HSPC) were detected in the blood early after infection. Mobilization of both immature and mature cells was accompanied by the reduction of BM SDF-1 (CXCL-12) levels and the reciprocal elevation of SDF-1 in the blood 24 h post infection. RT-PCR analysis of RNA collected from total BM cells revealed an early induction of myeloid-associated genes, suggesting a prompt commitment to myeloid lineage differentiation. These findings indicate that lung infection by Y. pestis is sensed by BM cells early after infection, although bacterial colonization of the BM occurs at late disease stages, and point on a potential cross-talk between the lung and the BM at early stages of pneumonic plague.